2002
DOI: 10.2134/jeq2002.1649
|View full text |Cite
|
Sign up to set email alerts
|

Soil‐to‐Root Transfer and Translocation of Polycyclic Aromatic Hydrocarbons by Vegetables Grown on Industrial Contaminated Soils

Abstract: Polycyclic aromatic hydrocarbons (PAHs) are possible contaminants in some former industrial sites, representing a potential risk to human health if these sites are converted to residential areas. This work was conducted to determine whether PAHs present in contaminated soils are transferred to edible parts of selected vegetables. Soils were sampled from a former gasworks and a private garden, exhibiting a range of PAH concentrations (4 to 53 to 172 to 1263 and 2526 mg PAHs kg-1 of dry soil), and pot experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
113
3
8

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(132 citation statements)
references
References 20 publications
8
113
3
8
Order By: Relevance
“…PAHs may be taken up through several pathways including the aerial absorption of volatile compounds by leaves, deposition and penetration of contaminated soil particles and dusts on leaves, and soil-to-root transfer of contaminants followed by subsequent translocation by the transpiration stream. However, root uptake is implicated as the main pathway for PAHs accumulation in plant tissues, particularly for HMWPAHs [17]. The highest biomass was noticed in the reference soil (T5), possibly because of its high value of WSOC and low pollution level for both PAHs and HMs as compared to wastewater-irrigated soils.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PAHs may be taken up through several pathways including the aerial absorption of volatile compounds by leaves, deposition and penetration of contaminated soil particles and dusts on leaves, and soil-to-root transfer of contaminants followed by subsequent translocation by the transpiration stream. However, root uptake is implicated as the main pathway for PAHs accumulation in plant tissues, particularly for HMWPAHs [17]. The highest biomass was noticed in the reference soil (T5), possibly because of its high value of WSOC and low pollution level for both PAHs and HMs as compared to wastewater-irrigated soils.…”
Section: Discussionmentioning
confidence: 99%
“…Plastic plates were placed at the height of plant shoots to collect the soil and dust particles for measuring the aerial supply of PAHs to shoot tissues. The leaf surface area and dust mass were calculated as proposed by Fismes et al [17]. To distinguish the PAHs uptake through root from aerial deposition, the soils were covered with uncontaminated sand to prevent the possible contact of leaf with soil, and also to minimize the evaporation of LMWPAHs.…”
Section: Design Of Pot Experimentsmentioning
confidence: 99%
“…In addition, many studies have demonstrated that the extractability and the bioavailability of PAHs decrease significantly with time in the aging processes (Northcott and Jones 2001;Luo et al 2012). Most PAHs released into the environment will finally enter into the soil ecosystem, where they will impair human and other organisms through the food chain (Fismes et al 2002). Therefore, it is of great importance to detect the effect of PAH pollution on certain bacterial populations associated with PAH degradation and seek appropriate bioindicators to reflect the impact of PAH pollution in aged industrial soils.…”
Section: Introductionmentioning
confidence: 99%
“…HOCs with high hydrophobicity in soils are strongly associated with soil and particularly with soil organic matter, and only a very limited fraction would be expected to be available for plant uptake (1,3). After uptake by roots, these compounds partition strongly onto the root epidermis and will be translocated to shoots with difficulty (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%